(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
Modern information and communication technologies (ICT) have become an integral part of early childhood education worldwide, transforming traditional pedagogical approaches and expanding opportunities for effective development of mathematical thinking in preschool children. This article examines the theoretical foundations, methodological principles, and practical strategies for implementing modern digital tools and interactive technologies in preschool mathematics lessons. The study synthesizes current research, classroom practices, and pedagogical innovations to explore how multimedia tools, interactive applications, digital games, augmented reality (AR), virtual manipulatives, adaptive learning systems, and robotic kits support early mathematical learning. Using the IMRAD structure, this article discusses the relevance of technology-enhanced learning (TEL), analyzes the effects of digital resources on children’s cognitive development, evaluates specific classroom methods, and compares outcomes between traditional and technologysupported lessons. The results demonstrate that well-designed technological interventions significantly improve numeracy skills, motivation, problem-solving abilities, spatial reasoning, and conceptual understanding in children aged 3–7 years. The findings highlight the need for teacher training, curriculum modernization, and thoughtful integration of digital tools aligned with developmental psychology. Recommendations are provided for educators, administrators, and researchers, emphasizing play-based, safe, and ageappropriate use of modern technologies to enrich mathematics instruction in preschool environments.